Sustainable finance: how does zakat management matter? - Habibullah, Mohammad; Haron, Razali (Routledge, 2024)
The goal of this study is to present a broad explanation on the idea of effective zakat governance, utilizing its management as a significant remedy in the pervasive financial crisis of today. The objective of this research is to investigate the effects of excellent governance on zakat administration because it is a requirement for a good society. A set of social policies that are focused on zakat management, a vibrant private sector, and broad-based economic growth are all required for good governance. From an Islamic perspective, it is essential to carefully implement excellent authority in order to maximize social and economic growth. Islam offers rules for social, political, and economic institutions since it is a complete code of life. Therefore, Islam is concerned with collecting zakat and ensuring that its entire populace has a decent existence through an ongoing welfare program that is necessary for all Muslims. As a result, Islamic authorities must be concerned with maintaining economic stability and steady growth in order to prevent a decline in their subjects' level of living. So, delivering and implementing rules and obligations in the best way is effective governance. The Shari'ah protects justice for the general public and encourages ethical behavior in all spheres of life, hence the goal of the Islamic system of good governance is to end social injustice, eliminate corruption, and promote public welfare. Data gathering techniques include reading and researching in libraries, as well as analyzing the content of primary and secondary sources.